2017
DOI: 10.1530/joe-16-0657
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein (HDL) metabolism and bone mass

Abstract: It is well appreciated that high density lipoprotein (HDL) and bone physiology and pathology are tightly linked. Studies, primarily in mouse models have shown that dysfunctional and/or disturbed HDL can affect bone mass through many different ways. Specifically, reduced HDL levels have been associated with the development of an inflammatory microenvironment that affects the differentiation and function of osteoblasts. In addition, perturbation in HDL metabolic pathways favor adipoblastic and restrain osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 99 publications
(76 reference statements)
1
42
0
3
Order By: Relevance
“…The role of APOE in bone metabolism is puzzling, yet intriguing [11]. Indeed, morphologic and histomorphometric experiments on KO mice have shown that APOE deficiency is associated with elevated bone mass and increased osteoblastic function [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of APOE in bone metabolism is puzzling, yet intriguing [11]. Indeed, morphologic and histomorphometric experiments on KO mice have shown that APOE deficiency is associated with elevated bone mass and increased osteoblastic function [16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APOA1 knockout (KO) mice are characterized by augmented bone marrow adiposity, a finding that highlights the importance of bone marrow white fat in the regulation osteoblastic function and thus bone mass maintenance [10]. Other components of the HDL metabolic cassette, namely the lipid transporter, ATP-binding cassette 1 (ABCA1) and the major HDL receptor scavenger receptor class B type I (SRB1) have also been found to be differentially involved in the pathobiology of OP [11].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the bone mineral content may be an important approach used to diagnostic of metabolic diseases, especially in post-menopausal and advanced-age women, due to the risk of osteoporosis and consequently fractures [35,36]. Recent findings also have demonstrated that in an obesity condition there is an increase of the alveolar bone loss, a reduction of the bone mineral density, an imbalance in bone remodeling with deterioration of trabecular bone structure, indicating a closed relationship between the overweight with osteoporosis and facture risk as well as with the energy metabolism [37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that certain species of HDL, but not others, provide protection against CAD, and that the genetic or drug perturbations failed to impact those mediating the protection. In particular, certain population studies have found that the efficiency of HDL in mediating cholesterol efflux from cells has been associated with decreased incidence of CAD (Khera et al, 2011;2017;Rohatgi et al, 2014). In addition to CAD, HDL is likely to mediate a variety of immune and regulatory functions (Barter, 2004;S.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to CAD, HDL is likely to mediate a variety of immune and regulatory functions (Barter, 2004;S. M. Gordon and Remaley, 2017;Kypreos, 2017). Since these protective functions are likely regulated by the proteins associated with HDL, understanding the regulation of HDL subpopulation's proteome heterogeneity is an imperative.…”
Section: Introductionmentioning
confidence: 99%